Physiological demand of esports athletes : Tuntutan Fisiologis Atlet Esports - Agus, Herdiansyah; Patty, Maleaky; Utama.J, Eko Putra; Cahyo, Dito Dwi; Santoso, Bayu; Saputra, Yudhi Esa; Aliansyah, Hadiat (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
This study aims to reveal the physiological demands on esports athletes when competing. To achieve this goal, a literature review was conducted on Scopus databases using Specific inclusion criteria between 2006 and 2024. 5 articles were selected for this review based on the relevance of the topics reviewed. Based on the articles, for esports athletes, it was found that the maximum oxygen uptake demand was 41.98 ± 5.50 mL/kg/min or the highest up to 48 mL/kg/min, while the demand for oxygen consumption at gameplay was found at an average of 3.89 mL/kg or a median of 0.29 (0.24-0.35) L/min. Furthermore, the maximum heart rate was 191 ± 10 beats/min (at aerobic maximum test) or 136.8 ± 13.3 beats/min (at gameplay). While the average heart rate when playing the game was between the median 87.1 (80.3 - 104) beats/min to the average 110.1 ± 15.7 beats/min. Based on this data, it can be understood the physiological response of esports athletes in game situations, which can be adjusted later to the dose of training provided (athlete adaptation to match needs). In addition, data on the physiological demands of esports athletes can also be used as a minimum target for the ability of esports athletes to be used as a benchmark. To prepare athletes to be physiologically ready for the match.